The Antibacterial Efficacy of Biopure MTAD in Root Canal Contaminated with Enterococcus faecalis. (6th September 2012) - Kamberi, Blerim; Bajrami, Donika; Stavileci, Miranda; Omeragiq, Shuhreta; Dragidella, Fatmir; Koçani, Ferit
Abstract : Aim . The purpose of this in vitro study was to assess the antimicrobial efficacy of Biopure MTAD against E. faecalis in contaminated root canals. Materials and Methods . Forty-two single rooted extracted human teeth were inoculated with E. faecalis and incubated for four weeks. The samples were divided in two control and five experimental groups irrigated with 1.5% sodium hypochlorite solution (NaOCl); 3% NaOCl; BioPure MTAD; 1.5% NaOCl/17% EDTA; or 3% NaOCl/17% EDTA. After a one-week incubation, complete disinfection was confirmed by the absence of turbidity in the incubation media. Dentin shavings were taken from samples with no turbidity to verify whether E. faecalis was present in dentin tubules. Results were analyzed statistically using Fisher's exact test, with the level of significance set at P < 0.05 . Results . Statistical analysis of the data obtained at Day 7 and after dentin shaving analysis showed that BioPure MTAD had significantly greater antibacterial activity than 1.5% NaOCl, 1.5% NaOCl/17% EDTA and 3% NaOCl/17% EDTA. No significant difference was detected between MTAD and 3% NaOCl. Conclusions . These findings suggest that BioPure MTAD possesses superior bactericidal activity compared with NaOCl and EDTA against E. faecalis .